Potential benefits of spinal cord stimulation treatment on quality of life for paralyzed patients with spinal cord injury - Xiang-Ling Huang; Yu-Chen Chen; Chang-Chih Kuo; Sheng-Tzung Tsai (Tzu Chi Medical Journal)
Spinal cord injury (SCI) is a severe central nervous system injury that can cause sensory or motor dysfunction. Although mortality rates for people with spinal cord injuries have dropped dramatically with advances in medicine, chronic long-term sequelae after SCI persist. The most bothersome problems reported by patients include pain, spasticity, urinary dysfunction, and loss of motor function. Thus, quality of life (QoL) is an essential issue in chronic SCI. Spinal cord stimulation (SCS) applies an adjustable, nondamaging electrical pulse that can reduce uncomfortable comorbidities and improve mobility, thus enhancing the QoL of patients with SCI. This review summarizes pivotal breakthroughs from SCS for individual clinical impairment from SCI. We conclude that careful evaluation of SCS can help improve neuropathic pain, spasms, motor symptoms, and voiding dysfunction in patients with SCI, thus improving QoL.